Prosedur Eksekusi atas Tindakan Wanprestasi dalam Jaminan Kredit Fidusia Pasca Putusan Mahkamah Konstitusi No. 18/PUU-XVII/2019 - Rachmatul Istiqomah; Imam Suroso (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Fiduciary collateral as a type of collateral gives the rights of executorial to creditors to do parate execution on the object of fiduciary collateral when a debtor defaults. In practice, however, collateral misuses this right illegally. This becomes the basics for Judicial Review agains Article 15, paraghraphs 2 and 3 of Law No. 42/1999, and the Constitutional Court issued the Ruling No. 18/PUU-XVII/2019. Therefore in this thesis the formulation of the problem raised is first, when a debtor is considered to have committed an act of default, and secondly, it delves into the creditor's execution procedure and the ratio decidendi related to Constitutional Court Decision No. 18/PUU-XVII/2019. The research use descriptive juridicial normative method. The data were gathered by conducting library research. The result of the analysis shows that Ruling does not impede the right of executing by creditors so that it is in accordance with the executorial right in fiduciary collateral. So, there are two possible ways for a debtor to be declared in default: firstly, the agreement of default is stipulated during the main agreement and the initial fiduciary collateral agreement. Secondly, the default is determined by the district court in order to execute the fiduciary collateral object.